ChemInform Abstract: Isolation of Three New Annonaceous Acetogenins from Graviola Fruit (Annona muricata) and Their anti‐Proliferation on Human Prostate Cancer Cell PC‐3. Issue 51 (5th December 2016) - Sun, Shi; Liu, Jingchun; Zhou, Ninghui; Zhu, Wenjun; Dou, Q. Ping; Zhou, Kequan
Abstract: The three new annonaceous acetogenins, muricins M (I) and N (II), and muricenin (III), are isolated from the fruit powder of Graviola (Annona muricata).